The keeper - Gioni, Massimiliano 1973-; Bell, Natalie 1967- (New Museum, 2016)
Artists' projects and texts concerned with the impulse to "collect," and how this undertaking may define, inspire, and chronicle the individual colector
Published on the occasion of the exhibition "The Keeper", New Museum, New York, NY, July 20-September 25, 2016
Keywords: Art / 21st century / Exhibitions; Collectors and collecting / Exhibitions; Art objects / Collectors and collecting / Exhibitions; Art; Art objects / Collectors and collecting; Collectors and collecting; Kunst; Art brut; Sammler; Ausstellungskatalog; Ausstellungskatalog -- New Museum of Contemporary Art -- 20.07.2016-25.09.2016 -- New York, NY; Bildband